Pendidikan Akhlak Menurut Syekh Kholil Bangkalan - Salsabila, Krida; Firdaus, Anis Husni (Jurnal Penelitian Pendidikan Islam, 2018)
The research aims to elaborate the thoughts of Sheikh Kholil Bangkalan about moral education. This research is considered important considering the ethical problems faced by modern society are very serious. Sheikh Kholil Bangkalan is an Indonesian cleric whose thoughts, attitudes, and behavior have a significant influence on Muslims in the country, especially in Bangkalan Land. By using the content analysis method, this study produced a number of findings, that according to Syekh Kholil Bangkalan, one of the goals of education is to make learners have noble character, namely the change of behavior of learners to a better direction. The purpose of this education is at the same time a concrete form of the ultimate goal of education, that is, faith and piety to God Almighty